Liutprand z Cremony o magii połabskich SłowianLiudprand of Cremona on Polabian Slavic Magic - Łuczyński, Michał (Studia mythologica Slavica, 2016)
<span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">The author analyses Liudprand of Cremona’s Report of his Mission to Constantinople (in 968), a neglected source text on the history of Slavic Pagan Religion. This article is devoted to the interpretation of the Pre-Christian Slavic summer fests mentioned in the work of Liudprand. According to the author it shows the practices and beliefs of Morzyczanie, one of the West Slavic tribes conquered by Otto I.